Class war or race war - Kende, Tamás (Historian), author.
1 online resource (vi, 194 pages).
Keywords: "Class War or Race War is more than an anti-thesis of the master-narrative regarding the Soviet state antisemitism. Kende not only refutes the originally anti-Communist myth of the systemic nature of (state) socialism, but tries to re-, and deconstruct the origins of this myth. With intensive use of historical documents, memoirs and the related historiography, the book attempts to make historical sense from the myth it intends to refute. Kende goes beyond the contemporary perceptions of the "Jewish question" and antisemitism and with close reading of original documents, reconstructs the real frontlines of the Soviet society of the 1940s, which were not constructed along identity-political lines. The book reinvests the long forgotten understanding of social classes in an allegedly classless and monolithic society. The spontaneous formations of the actual frontlines in the hinterland, or on the actual fronts (battlefields, in the Red Army) lacked the participants' class consciousness, thus its occurrences in the form of conflict producing historical records were recorded as acts of antisemitism. As the book advocates, Jews could have been found on both sides of the inner frontlines of the Soviet society during, and right after the WWII. An insightful read for scholars of Soviet history, that presents a bold and challenging interpretation of the regime and its flaws - both perceived and real"--